Copyright Versus Open Access: On the Organisation and International Political Economy of Access to Scientific Knowledge - Scheufen, Marc (Springer, 2016)
This book addresses the recent debate about copyright law and its impact on the distribution of scientific knowledge from an economic perspective. The focus is on the question whether a copyright regime or an open access regime is better suited to the norms and organizational structure in a purely global science community. The book undertakes a thorough economic analysis of the academic journal market and showcases consequences of a regime change. It also takes account of the Digital Divide debate, reflecting issues in developing countries. Finally, a comprehensive analysis of legal action in the light of international Intellectual Property (IP) agreements offers prospects on the future of academic publishing.